Elemen Tradisional dalam Desain Interior: Pengaruh Tata Letak dan Fungsi dalam Rumah Adat Miduana - Maulana, Teddy Ageng (Ideas Publishing, 2024)
Traditional interior design often reflects the integration of cultural elements and practical functions in a residential context. This study aims to explore the influence of traditional elements on the layout and function of space in the traditional house of Kampung Miduana, Cianjur. Using a qualitative approach with a case study method, this study analyzes the door orientation, the function of the gowah and parukuyan, and the design of the stilt house. The findings show that the south door orientation combines symbolism and practical functions, the gowah and parukuyan have deep cultural values, and the design of the stilt house reflects the harmony between aesthetics and functional needs. The implication of this study is the importance of considering traditional elements in contemporary interior design to maintain and express local cultural identity.